Prior Dengue Virus Infection Is Associated With Increased Viral Load in Patients Infected With Dengue but Not Zika Virus. (12th July 2019) - Santiago, Gilberto A; Sharp, Tyler M; Rosenberg, Eli; Sosa Cardona, Iris I; Alvarado, Luisa; Paz-Bailey, Gabriela; Muñoz-Jordán, Jorge L
Abstract: To evaluate potential enhancement of Zika virus (ZIKV) infection among patients with prior dengue virus (DENV) infection, we compared loads of viral RNA among patients infected with ZIKV (n = 1070), DENV-2 (n = 312), or DENV-3 (n = 260). Compared to patients without prior DENV infection, patients with prior DENV infection had significantly higher mean loads of viral RNA if infected with DENV-2 (10.6 vs 11.6 log10 GCE/mL, respectively; t test, P < .0001) or DENV-3 (10.3 vs 10.9 log10 GCE/mL; P < .0001), but not ZIKV (4.7 vs 4.7 log10 GCE/mL; P = .959). These findings provide evidence against in vivo enhancement of ZIKV by anti-DENV antibodies. Abstract : Prior dengue virus infection is associated with higher viral load in patients with dengue, but not Zika virus, disease.